The Effects of Sandstorms on the Climate of Northwestern China - Tiantian Hu; Di Wu; Yaohui Li; Chenghai Wang (Advances in Meteorology)
In this paper, we investigate the observational direct radiation characteristics of several sandstorm events in Northwestern China (NWC). A simulating sensitivity experiment was designed to reduce the downward radiation in RegCM4 to investigate the climatic impacts and persistence of the direct radiation effect (DRE) from dust aerosols in sandstorms. The results show that dust aerosols in sandstorms can change the radiation heating rate of the atmosphere, heating the air in the middle and low troposphere and cooling Earth’s surface. The climate effects of continuous and intense sandstorms in April in NWC can reach downstream areas such as Southeast and Northeast China and can persist for months. The dust aerosols in sandstorms can enhance diabatic heating and moisture loss. Therefore, dust storms lead to the environment in NWC becoming warmer and dryer. Through analysis of the dust tracer total burden, we identified that the enhancement of the dust total burden in the arid region illustrated that the DRE of dust aerosol in sandstorm process can react with the dust emission, thus forming a self-feedback loop. The DRE can persist three months.